If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n(n + -2) = 8 Reorder the terms: n(-2 + n) = 8 (-2 * n + n * n) = 8 (-2n + n2) = 8 Solving -2n + n2 = 8 Solving for variable 'n'. Reorder the terms: -8 + -2n + n2 = 8 + -8 Combine like terms: 8 + -8 = 0 -8 + -2n + n2 = 0 Factor a trinomial. (-2 + -1n)(4 + -1n) = 0Subproblem 1
Set the factor '(-2 + -1n)' equal to zero and attempt to solve: Simplifying -2 + -1n = 0 Solving -2 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1n = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1n = 0 + 2 -1n = 0 + 2 Combine like terms: 0 + 2 = 2 -1n = 2 Divide each side by '-1'. n = -2 Simplifying n = -2Subproblem 2
Set the factor '(4 + -1n)' equal to zero and attempt to solve: Simplifying 4 + -1n = 0 Solving 4 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1n = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1n = 0 + -4 -1n = 0 + -4 Combine like terms: 0 + -4 = -4 -1n = -4 Divide each side by '-1'. n = 4 Simplifying n = 4Solution
n = {-2, 4}
| 7z^2-z-8=0 | | (X-5)/(X-6)=56 | | (X-5)(X-6)=56 | | 5x^4/10 | | 1000x^2-100x=0 | | 6x+2y+3y=11 | | (D^4+4D^2)y=96x^2 | | 2x11/4=13 | | (5.6x+2)(5.6x-2)= | | 25x^2+9y^2-18y-216=0 | | (0.6x-1.28)(18x+8)= | | 72=4x-12 | | 2m(n+3)-m(2n+1)= | | 2e^x/8e^-x | | X+0.6x=250y | | -5x+10=14+(4+x) | | g+7f=16 | | 12=3*x | | 4x^2+x=44 | | 9x+-9y=27 | | f(x)=10x-18 | | 4x^2+x-44=0 | | 50-(30+80)= | | u-v+6u-3v= | | (3x-4)(x-20)=3x(x-9)-3 | | 2-3(7x+9)=6 | | 5n^2+n-5=0 | | N+4=3n+16 | | -5t^2+40t+20= | | 0.2r-1.3r+0.6=-0.9+3.6 | | 19/2/3 | | 2/3/18 |